Ocular adverse events associated with anti-VEGF therapy: A pharmacovigilance study of the FDA adverse event reporting system (FAERS) - Ma, Pan; Pan, Xinmei; Liu, Ruixiang; Qu, Ya; Xie, Linli; Xie, Jiangchuan; Cao, Liya; Chen, Yongchuan (Frontiers in Pharmacology, 2022)
Background: The purpose of this study is to identify and characterize ocular adverse events (AEs) that are significantly associated with anti-VEGF drugs for treatment of neovascular age-related macular degeneration and compare the differences between each drug, and provide clinical reference. Methods: Ocular AEs submitted to the US Food and Drug Administration were analyzed to map the safety profile of anti-VEGF drugs. The Pharmacovigilance tools used for the quantitative detection of signals were reporting odds ratio and bayesian confidence propagation neural network. Results: A total of 10,608,503 AE reports were retrieved from FAERS, with 20,836 for ranibizumab, 19,107 for aflibercept, and 2,442 for brolucizumab between the reporting period of Q1, 2004 and Q3, 2021. We found and analyzed the different AEs with the strongest signal in each drug—ranibizumab-macular ischaemia (ROR=205.27, IC-2SD=3.70), retinal pigment epithelial tear (ROR=836.54, IC-2SD=7.19); aflibercept-intraocular pressure increased (ROR=31.09, IC-2SD=4.61), endophthalmitis (ROR=178.27, IC-2SD=6.70); brolucizumab-retinal vasculitis (ROR=2930.41, IC-2SD=7.47) and/or retinal artery occlusion (ROR=391.11, IC-2SD=6.10), dry eye (ROR=12.48, IC-2SD=2.88). Conclusions: The presence of AEs should bring clinical attention. The use of anti-VEGF drugs should be based on the patient's underlying or present medical condition to reduce any adverse event associated with the treatment.